Pengaruh Harga Jual terhadap Volume Penjualan Sapi Potong ditingkat Pedagang Pengecer - Pateda, Sry Yenni; Rokhayati, Umbang Arif (Gorontalo Journal of Equatorial Animals, 2023)
Price is one factor that is taken into account in marketing activities because price can determine how much profit will be obtained from the sale of beef cattle. The purpose of this study was to determine the sales volume and selling price of beef cattle at the Pulubala animal market, and the effect of the selling price on the selling volume of beef cattle at the Pulubala animal market. This research was carried out for 2 months, namely October-December 2022 at the Pulubala animal market, Gorontalo Regency. The research method used is the survey method by collecting primary data and secondary data. Data analysis used to determine sales volume and selling price is descriptive analysis and simple linear regression analysis is used to determine the effect of selling price on beef cattle sales volume. The results showed that the sales volume of beef cattle at the Pulubala animal market in Gorontalo Regency showed that the lowest livestock sales were 36 heads and the highest was 53 heads with an average of 42 heads per week. The selling price of beef cattle is IDR 7,000,000 to IDR 18,000,000 with an average price of IDR 10,803,000 per head and has an average body weight of 155 kilograms. The effect of the selling price on the sales volume of beef cattle in the Pulubala animal market is 16%.